2021
DOI: 10.21608/tsnj.2021.210229
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Nurses Regarding Client Safety at Maternal and Child Health Care Centers

Abstract: Background: Patient safety is the cornerstone of high-quality health care. Nurses play a critical role in ensuring patient safety by monitoring patients, detecting errors, understanding care processes, and performing countless other tasks to ensure patients receive high-quality care. Aim of this study: Assess knowledge, attitudes and practices of nurses toward client safety at maternal and child health care centers (MCH). Subjects and methods: A Convenience sample of 120 nurses included in the study. Design: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…In the current study, 61% of the participants demonstrated a positive attitude towards PS. This percentage was higher than a study conducted in Ethiopia 16 but lower than a study conducted in Egypt [ 20 ]. The variations in percentages could be attributed to different settings and the implementation of positive initiatives and educational programs in certain healthcare centers more than our study health centers.…”
Section: Discussioncontrasting
confidence: 72%
“…In the current study, 61% of the participants demonstrated a positive attitude towards PS. This percentage was higher than a study conducted in Ethiopia 16 but lower than a study conducted in Egypt [ 20 ]. The variations in percentages could be attributed to different settings and the implementation of positive initiatives and educational programs in certain healthcare centers more than our study health centers.…”
Section: Discussioncontrasting
confidence: 72%